AN ANALYSIS OF CONSUMER’S EVALUATION TOWARDS PRICE BUNDLING (CASE STUDY : MCDONALD’S MANADO) - Poluan, Christian H. S.; Saerang, David P.E; Tumewu, Ferdinand J. (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: The fast-food consumption continues to increase in popularity, and consumers usually make evaluations based on their past personal experience. The purpose of this research is to know the result of consumer?s evaluation towards price bundling in McDonald?s Manado. This research is a qualitative analysis interview, the population in this research is the customers of McDonald?s Manado, and using the purposive sampling as the research method. The variables used in this research were taken from the literature to determine the result of consumer?s evaluation towards price bundling. The data were gathered through interview with the informants and examination of the literature review from previous researches. The result showed that all of the informants share the same opinion about price bundling that it really does affect their final thoughts about price bundling in McDonald?s Manado. The conclusion is the price bundling strategy works well, the variety of meal package really helps customers in making their decision when ordering their desired meal, and the customers also considered that the price for the meal package is rather cheaper. They stated that the meal package is well worth the price, the customers really satisfied with what the McDonald?s has to offer.Keywords: consumer?s evaluation, price bundling